Global estimate of phenotypic and genotypic ganciclovir resistance in cytomegalovirus infections among HIV and organ transplant patients; A systematic review and meta-analysis. (April 2020) - Azimi, Taher; Tavakolian, Shaian; Goudarzi, Hossein; Pourmand, Mohammad Reza; Faghihloo, Ebrahim
Abstract: Human cytomegalovirus (CMV), an opportunistic pathogen belonging to Herpesviridae family, is considered as one of the major causes of morbidity and mortality among wide variety of patients, particularly in transplant recipients and HIV positive patients. As this virus can be resistant to treatment, frequency of CMV in patients who receive organ transplantation and people suffering from AIDS was studied between 1980 and 2019. Medline (via PubMed), Embase, Web of Science, and the Iranian Database were reviewed, and Comprehensive Meta-Analysis (V2.0, Biostat) software analyzed all data. Finally, we used Cochran's Q-statistic to encounter heterogeneity between different studies. Meta-analyses indicated, GCV resistance was 14.1% (95% CI 11.2–17.7); however, in patients suffering from AIDS and organ transplantation were 19.5% (95% CI 14.7–25.4) and 11.4% (95% CI 8.1–15.8), respectively. There were increasing rates in the prevalence of GCV resistance in CMV among transplant recipients, and HIV positive patients. Therefore, evaluation of these refractory infections is beneficial. Highlights: CMV is considered as one of the major causes of morbidity and mortality among HIV and transplant recipients. GCV resistance in patients suffering from AIDS was 19.5% (95% CI 14.7–25.4). GCV resistance in patients suffering from organ transplantation was 11.4% (95% CI 8.1–15.8).